RsGSTF12 Contributes to Anthocyanin Sequestration in Radish (Raphanus sativus L.) - Niu, Mengyang; Bao, Changjian; Chen, Jiahui; Zhou, Wen; Zhang, Yueyue; Zhang, Xiaoyan; Su, Nana; Cui, Jin (Frontiers in Plant Science, 2022)
Anthocyanins are water-soluble plant pigments mainly stored in the plant vacuoles. Glutathione S-transferases (GSTs) are a multifunctional enzyme family, which can regulate substance metabolism and biological and abiotic stresses in plants. However, few reports were focused on the involvement of GSTs in anthocyanin sequestration in red skin radish. Here, we identified a glutathione S-transferase gene RsGSTF12 that played roles in anthocyanin sequestration in radish. The bioinformatics analysis revealed that RsGSTF12 belonged to the phi (F) class of glutathione S-transferases and showed high homology with AtGSTF12, followed by AtGSTF11. The subcellular localization assay showed that RsGSTF12 located to the endoplasmic reticulum and tonoplast. Temporal and spatial gene expression-specific analyses uncovered a strong correlation of RsGSTF12 to anthocyanin accumulation in radish sprouts. The anthocyanin solubility assay found RsGSTF12 was capable of improving cyanidin water solubility in vitro. Transiently expressing RsGSTF12 in radish cotyledons was able to increase their anthocyanin sequestrations. Furthermore, the functional complementation and overexpression of the Arabidopsis thaliana tt19 mutant and wild type demonstrated that RsGSTF12 might play an indispensable role in anthocyanin accumulation in radish. Taken together, we provide compelling evidence that RsGSTF12 functions critically in how anthocyanins are sequestrated in radish, which may enrich our understanding in mechanism of anthocyanin sequestration.